2015
DOI: 10.1002/chem.201500988
|View full text |Cite
|
Sign up to set email alerts
|

Pyridyl‐Functionalised 3H‐1,2,3,4‐Triazaphospholes: Synthesis, Coordination Chemistry and Photophysical Properties of Low‐Coordinate Phosphorus Compounds

Abstract: Novel conjugated, pyridyl-functionalised triazaphospholes with either tBu or SiMe3 substituents at the 5-position of the N3 PC heterocycle have been prepared by a [3+2] cycloaddition reaction and compared with structurally related, triazole-based systems. Photoexcitation of the 2-pyridyl-substituted triazaphosphole gives rise to a significant fluorescence emission with a quantum yield of up to 12 %. In contrast, the all-nitrogen triazole analogue shows no emission at all. DFT calculations indicate that the 2-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 70 publications
0
39
0
3
Order By: Relevance
“…Interestingly, the reaction of pyridotetrazole with t Bu-phosphaalkyne P¸C t Bu turned out to proceed smoothly and selectively toward the desired product 40, and was already completed after 2 h at T = 65°C (Scheme 13). 53 Similarly, the SiMe 3 -substituted triazaphosphole 41 was formed within 1 h by reaction of the pyridotetrazole and P¸C SiMe 3 in toluene. The SiMe 3 group was found to have a rather large influence on the chemical shift of the product, as the phosphorus resonance in the 31 P{ 1 H} NMR spectrum of compound 41 was observed at ¤ = 211.6 ppm, while compound 40 shows a resonance at ¤ = 167.5 ppm in the 31 P{ 1 H} NMR spectrum.…”
Section: Pyridyl-functionalized 3h-1234-triazaphospholesmentioning
confidence: 99%
“…Interestingly, the reaction of pyridotetrazole with t Bu-phosphaalkyne P¸C t Bu turned out to proceed smoothly and selectively toward the desired product 40, and was already completed after 2 h at T = 65°C (Scheme 13). 53 Similarly, the SiMe 3 -substituted triazaphosphole 41 was formed within 1 h by reaction of the pyridotetrazole and P¸C SiMe 3 in toluene. The SiMe 3 group was found to have a rather large influence on the chemical shift of the product, as the phosphorus resonance in the 31 P{ 1 H} NMR spectrum of compound 41 was observed at ¤ = 211.6 ppm, while compound 40 shows a resonance at ¤ = 167.5 ppm in the 31 P{ 1 H} NMR spectrum.…”
Section: Pyridyl-functionalized 3h-1234-triazaphospholesmentioning
confidence: 99%
“…This decomposition was monitored by at emperature dependent 31 PNMR from À40 8 8Ct o8 0 8 8C( Supporting Information), which showed that two products are formed. Thef irst reaction step is the adduct formation, which leads to the phosphadiazadiene (I2), similar to 2,a fter migration of a[ W(CO) 5 ] group.T his phosphadiazadiene reacts with as econd diazomethane by a[ 2 + +3] cycloaddition and the migration of a[ W(CO) 5 ]g roup to 6a.I ng eneral, triazaphospholes are obtained by the reaction of phosphaalkenes [17] or phosphaalkynes [18] with an azide (RN 3 ). [14] Them olecular structure of 2 is shown in Figure 2.…”
mentioning
confidence: 93%
“…However replacing the 2‐pyridyl group with a 3‐pyridyl or a phenyl group greatly reduces the quantum yields. In summary, for highly emissive properties position of the nitrogen atom as well as the presence of the phosphorus atom in the triazole ring are critical …”
Section: Cyclic Structures Containing Phosphorus and Other Heteroelemmentioning
confidence: 99%
“…In summary,f or highly emissive properties position of the nitrogen atom as well as the presence of the phosphorus atom in the triazole ring are critical. [87]…”
Section: Phospholes With More Than One Heteroatommentioning
confidence: 99%